Stark effect for relativistic heavy li-like ions planar channeled in a crystal, resonant coherent excitation and corresponding radiation; RREPS-15. Radiation from Relativistic Electrons in Periodic Structures - Sinitsyn E. Evgeny (Poster Session, 2015)
Title screen.